Strategies and Policies to Strengthen Economic Growth in the Middle East and North Africa Region - Razak, Andi Muhammad Yaqub (Professorline, 2024)
This paper aims to analyze strategies and policies that can improve economic growth and development in the Middle East and North Africa (MENA) region. This study uses a regional and comparative approach to identify the factors influencing a region's economic performance. Research results show that the Middle East and the Middle East have great potential to improve economic growth and development by exploiting natural resources, human capital, trade, investment, and regional integration. The region faces political conflict, social instability, income inequality, corruption, and a lack of structural reforms. This study, therefore, recommends some strategies and policies that MENA countries can implement to overcome these barriers and create an environment conducive to economic growth and development.